Respiratory endoscopy - Izumo, Takehiro; Sasada, Shinji; Aso, Tomohiko; Nasu, Kazuko; Arai, Yasuaki (Singapore : Springer, 2017)
This book provides a detailed overview of the latest innovations in respiratory endoscopy, from both diagnostic and therapeutic perspectives; each chapter focuses on one disease and the techniques for early diagnosis as well as treatment. It comprehensively covers treatment and procedures, including simultaneous X-ray fluoroscopy and its use during bronchoscopic procedures. This fast-developing technology is essential for the medical management of non-malignant and malignant diseases of the chest, especially lung cancer. Respiratory Endoscopy describes the cooperation between all the members of the healthcare team, and as such is a valuable resource not only for medical staff, but also for radiological technicians and nursing staff who contribute significantly in the care of the patients undergoing these invasive procedures. By promoting teamwork and providing practical know-how, it will improve the success and safety of respiratory endoscopy procedures.
Part I Edition for Radiological Technicians -- 1. The Role of X-ray Fluoroscopy in Bronchoscopy -- 2. Development of X-ray Fluoroscopy Devices -- 3. Characteristics of X-ray Fluoroscopy -- 4. Image Processing of X-ray Fluoroscopy and New Digital Tomography -- 5. Quality Control in X-ray Fluoroscopy and Digital Tomography -- 6. Computed Tomography Imaging to Bronchoscopic Navigation -- Part II Edition for Doctors -- 7. Fluorographic and Radiographic Conditions in Bronchoscopy Using X-ray Fluoroscopy -- 8. Identification of the Involved Bronchus to Peripheral Pulmonary Lesions on Computed Tomography -- 9. Anesthesia for Bronchoscopy -- 10. Processing Samples -- 11. Rapid On-site Cytology Evaluation -- 12. Type and Selection of Flexible Bronchoscope -- 13. Latest in Bronchoscopy (Hi-Vision Scope with Rotation Function) -- 14. Basic Flexible Bronchoscopy -- 15. Tomography-Guided Transbronchial Biopsy for Peripheral Pulmonary Lesions -- 16. Radial Endobronchial Ultrasound Findings -- 17. Radial EBUS Findings for Ground Glass Opacity: Comparison of Radiologic and Pathologic Findings -- 18. Endobronchial Ultrasound with a Guide Sheath for Peripheral Pulmonary Lesions -- 19. Transbronchial Needle Aspiration Through a Guide Sheath for Peripheral Pulmonary Lesions -- 20. Virtual Bronchoscopic Navigation for Peripheral Pulmonary Lesions -- 21. Virtual Bronchoscopic Simulation by CT Workstation -- 22. The Dose and Risk Factors for Radiation Exposure from X-ray Fluoroscopy during EBUS-GS for Peripheral Pulmonary Lesions -- 23. Endobronchial Ultrasound-guided Transbronchial Needle Aspiration -- 24. Endobronchial Ultrasound Elastography -- 25. Flex-rigid Pleuroscopy under Local Anesthesia -- 26. Stent Placement Under X-ray Fluoroscopy -- 27. Therapeutic Bronchoscopy for Central Airway Obstruction (Balloon, Argon Plasma Coagulation, High Frequency) -- 28. Endoscopic Bronchial Occlusion With Silicone Spigots -- 29. Photodynamic Therapy for Lung Cancer -- Part III Edition for Nurses -- 30. Actual Nursing in Respiratory Endoscopy.
Includes bibliographical references.
Keywords: Bronchoscopy; Lungs -- Diseases -- Diagnosis; Respiratory organs -- Diseases; Oncology; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Bronchoscopy; Lungs -- Diseases -- Diagnosis; Oncology; Respiratory organs -- Diseases; Electronic book; Electronic books